DINAMIKA SOSIAL EKONOMI MASYARAKAT SEKITAR HUTAN DALAM HUBUNGANNYA DENGAN MODEL PENGELOLAAN HUTAN PRODUKSI DAN SISTEM TPTII DALAM KERANGKA REDD (PERENNIAL, 2009)
This study was conducted in the area of Intensive Silviculture/ TPTII of PT Sari Bumi Kusuma in Central Kalimantan. Research purposes to analyze the impact and build social economic activities from TPTII silvicultural systems in the scope of carbon trading. The results of the analysis showed that the increase of TPTII activities lead to the increasing recognition of indigenous people and make condusive certainty of the business. However, the employment negatively correlated to the size of planting area, the minimum life needs are still at least low compared with the poverty standard of the World Bank. Based on the results of the analysis and projections indicate that scenario increasing community development/ PMDH and implementation of a continuous TPTII can press shifting cultivation growing rate of deforestation and degradation in the year to 50, as compared to no guidance of other parties and TPTII activities. In term of Carbon Conservation that community love to plant attractively is rubber, meranti and tengkawang. Compensation value for carbon conservation feasible for the community of Rp. 380.000/month/family. To involve the community directly in conservation activities in the carbon framework of REDD, then suggested to the program within the community, increasing the number and skills of communities and local labor, desimination activities of TPTII to the community, and providing a compensation fund can be derived from the DR/Reforestation Fee or other source of funds.Key words: Customary recognition, conflict, business certainty, carbon conservation, compensation